The cytomegalovirus egress proteins pUL50 and pUL53 are translocated to the nuclear envelope through two distinct modes of nuclear import - Schmeiser, Cathrin; Borst, Eva; Sticht, Heinrich; Marschall, Manfred; Milbradt, Jens (Journal of general virology, 2013)
The nucleocytoplasmic export of cytomegaloviral capsids is regulated by formation of a multi-component nuclear egress complex (NEC), essentially based on viral proteins pUL50 and pUL53. In this study, the generation of recombinant human cytomegaloviruses, expressing tagged versions of pUL50 and pUL53, enabled the investigation of NEC formation in infected primary fibroblasts. For these recombinant viruses, a wild-type-like mode of pUL50–pUL53 interaction and recruitment of both proteins to the nuclear envelope could be demonstrated. Importantly, pUL50 was translocated from an initial cytoplasmic distribution to the nuclear rim, whereas pUL53 accumulated in the nucleus before attaining overall rim colocalization with pUL50. Specified experimental settings illustrated that pUL50 and pUL53 were subject to different pathways of intracellular trafficking. Importantly, a novel nuclear localization signal (NLS) could be identified and functionally verified for pUL53 (amino acids 18–27), whereas no NLS was present in pUL50. Analysis of amino acid replacement mutants further illustrated the differential modes of nuclear import of the two essential viral egress proteins. Taken together, our findings suggest a combination of classical nuclear import (pUL53) and interaction-mediated recruitment (pUL50) as the driving forces for core NEC formation and viral nuclear egress.